Ethane Dehydrogenation with CO2 as a soft oxidant over a Cr-TUD-1 catalyst. Issue 39 (July 2020) - Numan, Muhammad; Kim, Taeho; Jo, Changbum; Park, Sang-Eon
Graphical abstract: Highlights: Mesoporous silica supporting isolated Cr oxide was hydrothermally synthesized. Reduction of Cr6+ to Cr3+/Cr0 and sintering of CrOX are main causes of deactivation. CO2 enhance the inter-convertibility of Cr6+ ↔ Cr3+ but cannot prevent the sintering. Addition of a small amount of O2 enable redispersion of sintered Cr2O3 into isolated Cr6+ CO2-regeneration is not suitable due to their weak-oxidizing ability. Abstract: A Cr-TUD-1 catalyst was directly synthesized under hydrothermal conditions using triethanolamine as a template for mesopore formation, tetraethylorthosilicate as a silica precursor, and Cr(NO3 )3 as a chromium source. Dehydrogenation of ethane to ethylene (DHE) in the presence of CO2 as soft oxidant was investigated over the Cr-TUD-1 catalyst, which had a nanosponge structure and a surface area of ∼ 650 m 2  g −1, and in which Cr 6+ species were dominantly distributed in a form of monochromate. During DHE under N2, Cr 6+ underwent partial reduction to Cr 3+ /Cr° with concomitant formation of large-sized Cr2 O3 and CrCx particles. As a result, the Cr-TUD-1 catalyst was deactivated within 2 h due to both the diminish of chromium active sites and the formation of coke. Replacement of N2 with CO2 enhanced the catalyst stability and produced little coke, which was attributed to enhanced inter-convertibility of Cr 6+ and highly dispersed Cr 3+ and a reverse Boudouard reaction between coke and CO2 . Aggregated large Cr2 O3 nanoparticles could not be readily oxidized to Cr 6+ by CO2 . The addition of O2 to CO2 further enhanced catalyst lifetime because the oxygen contributed to the redispersion of sintered Cr2 O3 nanoparticles to form isolated Cr 6+ species.